Effects of Light Spectra on Morphology, Gaseous Exchange, and Antioxidant Capacity of Industrial Hemp - Cheng, Xia; Wang, Rong; Liu, Xingzhu; Zhou, Lijuan; Dong, Minghua; Rehman, Muzammal; Fahad, Shah; Liu, Lijun; Deng, Gang (Frontiers in Plant Science, 2022)
One of the most important growth factors in cannabis cultivation is light which plays a big role in its successful growth. However, understanding that how light controls the industrial hemp growth and development is poor and needs advanced research. Therefore, a pot study was conducted to investigate the effects of different colors of light, that is, white light (WL), blue light (BL), red light (RL), and 50% red with 50% blue mix light (RBL) on morphology, gaseous exchange and antioxidant capacity of industrial hemp. Compared with WL, BL significantly increase hemp growth in terms of shoot fresh biomass (15.1%), shoot dry biomass (27.0%), number of leaves per plant (13.7%), stem diameter (10.2%), root length (6.8%) and chlorophyll content (7.4%). In addition, BL promoted net photosynthesis, stomatal conductance, and transpiration, while reduces the lipid peroxidation and superoxide dismutase and peroxidase activities. However, RL and RBL significantly reduced the plant biomass, gas exchange parameters with enhanced antioxidant enzymes activities. Thus, blue light is useful for large-scale sustainable production of industrial hemp.